Ernest Renan (1823-1892): De islam door oriëntalistische ogen - Sandwijk, Annemarie van (Tijdschrift voor theologie, 2011)
This article examines French scholar Ernest Renan’s Orientalist studies to obtain a more complete idea of his legacy. While Renan became known in nineteenth-century Europe mainly as a source of inspiration for modern Christian theology, his Orientalist studies on Islam drew attention in the Arab world, most notably his dissertation on Muslim philosopher Ibn Rushd (1126-1198). It appeared in 1852 under the title Averroès et l’Averroïsme: Essai historique. Renan’s legacy to Arabic studies has not received the attention it deserves. The present article shows that Orientalist presuppositions about Arabic philosophy, as Dimitri Gutas described them, are indeed present in Renan’s work on Ibn Rushd. This observation becomes interesting in the light of the indispensable and moot role that Renan played in the Arab world’s rediscovery of Ibn Rushd at the end of the nineteenth century. The way in which Renan drew attention to Ibn Rushd and the legacy of his work had great impact on the reception and image of Ibn Rushd in the modern Arab world. The central message in Renan’s dissertation was that Arab science and philosophy fell into decline after Ibn Rushd’s death, at least to the extent that it had not already been classified as an off-shoot of Greek philosophy. Renan thought the term ‘Arab philosophy’ misleading because philosophy is foreign to Arab culture where Islam is widespread. Because, in Renan’s view, Islam was by definition an enemy of reason and free thought, he believed that it was impossible to do meaningful work in a Muslim environment. Given that idea, Renan typified Ibn Rushd as a solitary and non-believing freethinker of European origin who lived in continuous dread of persecution and whose work can be considered resistance to Islam. Renan’s view of Ibn Rushd is thus strongly coloured by his Orientalist view of Arab-Islamic philosophy.